Analysis of the methodology for rate determination in commercial transportation service of conventional and executive taxis - Duque E, Gabriela; Orellana O, Iván; Coello, Mateo; Cordero-Moreno, Daniel (Enfoque UTE, 2018)
An efficient transport service allows a society to have economic progress and improves quality of life. Part of this structure is the issue in the determination of pricing the service of it, thus, the incomes of the offeror and good service to the user can be guaranteed. In Ecuador, the National Traffic Agency establishes a methodology that considers the offer of kilometers and operating costs. However, this methodology does not establish how to get and analyse the information that feeds the model, this aspect can generate biases and subjectivities at the time to define the rate. This study seeks to detect deficiencies in the methodology and suggest the relevant changes as an alternative to it, for this a mixed approach is considered, which not only considers surveys but also instrumentation and hi-technology to measure fuel consumption, tire wear, distance traveled and number of passengers. Once the analysis of the methodology was developed, a new approach to information gathering was proposed; and to validate, an experiment was applied to a canton of the country, with this it was possible to obtain rates that better represent the reality of the sector under analysis.